2020
DOI: 10.21203/rs.3.rs-84177/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Value Chain Analysis of Smallholder Dairy Production in Debark District, Ethiopia

Abstract: IntroductionMilk production in Ethiopia is done largely by the smallholder farmers in the high lands and in low land areas of the country. However, the Ethiopian dairy production and market systems face severe constraints like poor genetics, insufficient access to proper animal feed and poor management practices all contribute to the low productivity levels. Similarly, dairy producers and downstream actors in the value chains face many challenges in getting milk to market. Hence this study analyzes dairy produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…The result from Table 5 indicated that for one additional contact of the extension agent, the level of output sales increases by 4.4%. This result is consistent with the findings of [22] who found that extension contact significantly and Agricultural Sciences positively influences the quantity of milk supply to the market.…”
Section: Determinants Of Milk Commercializationsupporting
confidence: 93%
See 1 more Smart Citation
“…The result from Table 5 indicated that for one additional contact of the extension agent, the level of output sales increases by 4.4%. This result is consistent with the findings of [22] who found that extension contact significantly and Agricultural Sciences positively influences the quantity of milk supply to the market.…”
Section: Determinants Of Milk Commercializationsupporting
confidence: 93%
“…The survey result revealed that the households being members of farmers' cooperatives increase the level of commercialization by 2.0%. This finding is consistent with the results of [22] which suggest that strengthening dairy cooperatives, can play an increased role in milk collection, processing, and supplying processed dairy products to consumers, would help to modernize the milk production and marketing system.…”
Section: Determinants Of Milk Commercializationsupporting
confidence: 91%